About That Life Barry Lopez and the Art of Community - Cheney, Matthew (punctum books, 2023)
Why write? Why ask a reader to give their time and attention to your words? How can writing be more than narcissism and self-aggrandizement? These questions were ones that the writer and naturalist Barry Lopez asked at the Bread Loaf Writers' Conference in the summer of 2000, and they are questions at the heart of About That Life, a meditation on matters of living, making, and seeking. While Lopez is best known for such works of nonfiction as the National Book Award-winning Arctic Dreams, Matthew Cheney brings our attention to the many works of short fiction that Lopez published throughout his life, demonstrating how they fit within Lopez's sense of ethical aesthetics. That sense is then set alongside the work of San Francisco's New Narrative writers, insights from David Hinton's translations of Tu Fu, the story of community arising around a pottery kiln in western Oregon, the beauties and contradictions of Sōetsu Yanagi's The Unknown Craftsman, and the implications of the right-wing mob attack on the U.S. Capitol - an event that occurred on what would have been Barry Lopez's 76th birthday. Through a collage of memoir, history, literary criticism, philosophy, aesthetic theory, and creative writing exercises, About That Life wonders how we might live and dream in a world that seems ever more cruel and destructive.